Europe’s farm to fork strategy and its commitment to biotechnology and organic farming: conflicting or complementary goals? - Purnhagen, Kai; Clemens, Stephan; Eriksson, Dennis; Fresco, Louise O.; Tosun, Jale; Qaim, Matin; Visser, Richard G. F.; Weber, Andreas P. M.; Wesseler, Justus H. H.; Zilberman, David (Trends in plant science, 2021)
The European Commission’s Farm to Fork (F2F) strategy, under the European Green Deal, acknowledges that innovative techniques, including biotechnology, may play a role in increasing sustainability. At the same time, organic farming will be promoted, and at least 25% of the EU’s agricultural land shall be under organic farming by 2030. How can both biotechnology and organic farming be developed and promoted simultaneously to contribute to achieving the Sustainable Development Goals (SDGs)? We illustrate that achieving the SDGs benefits from the inclusion of recent innovations in biotechnology in organic farming. This requires a change in the law. Otherwise, the planned increase of organic production in the F2F strategy may result in less sustainable, not more sustainable, food systems.
Gesehen am 07.07.2021